STRATEGI KOMUNIKASI KLINIK UTAMA LAVALEN MEDICA DALAM MEMBANGUN BRAND AWARENESS MELALUI INSTAGRAM - Angel Nabella Sydney Potonengan; Iin Soraya; Yogi Ariska (An Nafi': Multidisciplinary Science, 2025)
This research aims to explore the communication strategy implemented by Lavalen Medica, a regenerative health clinic, in building brand awareness through Instagram. Lavalen Medica focuses on stem cell-based treatment services, which are still relatively new, complex, and high-cost in Indonesia. Therefore, an educational communication approach is necessary to foster public trust. This study uses a descriptive qualitative method with data collected through in-depth interviews with internal teams responsible for managing digital communication. The findings show that Lavalen’s communication strategy includes fact finding, content planning, implementation using various Instagram features (feed, reels, stories, and Meta Ads), and regular evaluation through Meta dashboard and Instagram Insights. This strategy has proven effective in enhancing brand recognition, increasing audience engagement, and shaping a positive perception of Lavalen Medica as a modern and trusted health service provider.